The human genomes - McVean, Gil (Henry Stewart Talks, 2007)
The nature of genetic polymorphism, Single nucleotide polymorphisms, Differences between genomic regions, Differences between populations, Inferences about human history from genetic variation, Detecting natural selection
Archived at 2025/05/28